MEWFM 2023
DOI: 10.5742/mewfm.2023.95256018
|View full text |Cite
|
Sign up to set email alerts
|

Interfering Barriers to Postpartum Depression Screening among women in Saudi Arabia: A Phenomenological Study

Abstract: Background: During the postpartum period women are at critical risk for postpartum depression. However, with the continuous development of maternal health services this maternal mental health issue remains underdiagnosed. Aim: This study aimed to explore the barriers interfering with postpartum depression screening among postpartum women in the context of Saudi Arabia. Method: An interpretive phenomenological qualitative approach was conducted in a tertiary hospital in Saudi Arabia. A convenience sample of 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…The “enhance health education” theme revealed that providing education to women during the antenatal period could decrease their anxiety after delivery and reduce the stigma that is considered a barrier for depressed postpartum women to seek help ( Almutairi et al, 2022 ). To maximize the possibility of detecting PPD symptoms early, nurses and midwives should begin educating new mothers and other relatives about the characteristics and clinical manifestations of depression, as well as how to detect depression symptoms, as early as possible ( Saleh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The “enhance health education” theme revealed that providing education to women during the antenatal period could decrease their anxiety after delivery and reduce the stigma that is considered a barrier for depressed postpartum women to seek help ( Almutairi et al, 2022 ). To maximize the possibility of detecting PPD symptoms early, nurses and midwives should begin educating new mothers and other relatives about the characteristics and clinical manifestations of depression, as well as how to detect depression symptoms, as early as possible ( Saleh et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study revealed several significant obstacles, such as a lack of overall interest in research projects (40.2%), a lack of interest in completing research (38.6%), limited knowledge of the research process (36.2%), and insufficient time to complete research activities (24.4%). Despite highlighting these prevalent issues, the study's findings are limited to the specific context of Riyadh, which may not be entirely applicable to other regions within Saudi Arabia or beyond [39].…”
Section: Research Challenges During Pandemics and Best Practicesmentioning
confidence: 97%